Cholangiocyte senescence caused by lysophosphatidylcholine as a potential implication in carcinogenesis. (28th April 2015) - Shimizu, Rina; Kanno, Keishi; Sugiyama, Akiko; Ohata, Hiroki; Araki, Anna; Kishikawa, Nobusuke; Kimura, Yasuhiro; Yamamoto, Hiroya; Kodama, Masanobu; Kihira, Kenji; Tazuma, Susumu
Abstract Background The incidence of biliary tract cancer in patients with pancreaticobiliary maljunction or intrahepatic cholelithiasis is markedly high with undefined mechanism. In these diseases, biliary lysophosphatidylcholine (LPC) level is reportedly increased. This study investigated the influence of LPC on cholangiocytes focusing on cellular senescence and its potential contribution to carcinogenesis. Methods Cultured MMNK‐1, an immortalized human cholangiocyte was treated with LPC in vitro and its effect was evaluated. Results Lysophosphatidylcholine demonstrated cytotoxicity with generation of intracellular reactive oxygen species. Accordingly, LPC provoked oxidative DNA injury, whereas the gene expressions of DNA repair enzyme (OGG1, MUTYH, MTH1) remained unchanged. Interestingly, LPC caused global DNA hypomethylation, which is frequently observed in cancer tissues. Microarray analysis identified differentially regulated genes in response to LPC, which included the components of senescence‐associated secretory phenotype (SASP) including interleukin‐8 (IL‐8), IL‐6, transforming growth factor‐β and plasminogen activator inhibitor‐1. Significant induction of these genes was further confirmed by quantitative real‐time polymerase chain reaction. In addition to upregulation of p21 gene expression, senescence‐associated beta‐galactosidase activity, a widely used marker of cellular senescence was significantly induced by the treatment of LPC. Conclusions Based on these data, cholangiocyte senescence and SASP caused by LPC are potential pathogenic mechanisms in the development of biliary tract cancer.